Storytelling with Puzzle Media to Develop Critical Thinking Abilities in Early Childhood - Hasiana, Isabella; Mufidah, Elia Firda; Aisyah, Aisyah; Pamungkas, Aristya Septi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine the critical thinking abilities of young children through telling stories using puzzle media. So far, the storytelling method has only been used to develop abilities in language and cognitive aspects which are limited to knowledge and understanding. Current educational demands encourage students to be able to think more complexly and at a higher level than just understanding and knowledge. These skills are what are called high order thinking skills (HOTS). One of the skills that surrounds HOTS is critical thinking skills. Critical thinking skills can be developed from an early age. This research uses descriptive qualitative methods. Data was collected through observation, interviews and documentation for 5 (five) kindergartens. The research results show that storytelling using puzzle media has promising potential for developing critical thinking skills in early childhood. Telling stories using puzzle media can help children analyze information, evaluate ideas, and draw conclusions. This research provides a new contribution to the field of early childhood education, especially in the development of critical thinking skills. The findings from this research can be used by educators and parents to design more effective and enjoyable learning activities for young children.